Fly ash utilisation in grouting applications - Pekrioglu, A; Doven, AG; Tumay, MT (Amer Soc Civil Engineers, 2003)
In addition to many environmental benefits, fly ash utilization provides end products with superior engineering and physical qualities as well as economic benefits, considering the utilization potential in construction-related applications such as; cement production and concrete products in the form of highway pavement concrete, structural concrete, and roller compacted concrete, bricks, blocks and paving stones; artificial lightweight aggregate, structural fills or embankments, stabilization of waste materials, mineral filler in asphalt paving, flowable/structural fill and grouting mixes. The fly ash, being a cementitious coal combustion by-product, promises high volume utilization in grouting applications by addition of other mineral admixtures when necessary. The fly ash grouts provide required engineering performance in improving ground stability by increasing strength and shearing resistance as well as reducing the permeability of soils treated with enhanced technical, theological, durability and economic advantages over sand and cement grouts. The fly ash grout is also cost-effective when alternative suspension, emulsion or solution materials are considered. In this study, fly ash grout composite formed of various combinations of high volume fly ash, cement, lime and high range water reducing chemical admixture has been investigated to define short-term engineering performance in terms of physicochemical (chemical compound analysis, unit weight, void ratio, specific gravity, linear shrinkage, hydraulic conductivity) and mechanical properties (unconfined compressive strength and flexural strength), excluding durability as the long term engineering performance. The overall short-term engineering performance indicates high volume fly ash utilization potential in grouting applications.
3rd International Conference on Grouting and Ground Treatment -- FEB 10-12, 2003 -- NEW ORLEANS, LA